2019
DOI: 10.1093/pasj/psz021
|View full text |Cite
|
Sign up to set email alerts
|

A possible model for the long-term flares of Sgr A*

Abstract: We examine the effects of magnetic field on low angular momentum flows with standing shock around black holes in two dimensions. The magnetic field brings change in behavior and location of the shock which results in regularly or chaotically oscillating phenomena of the flow. Adopting fiducial parameters like specific angular momentum, specific energy and magnetic field strength for the flow around Sgr A*, we find that the shock moves back and forth in the range 60 -170R g , irregularly recurring with a time-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…The present results for cases with low resistivity of η = 10 −6 and 0.01 are very similar to those for the previous magnetized flow without resistivity (Okuda et al (2019)). Adopting the same parameters of the flow and magnetic field as the present study, they found that the centrifugally supported shock moves back and forth between 60 R g ≤ R ≤ 170R g and that another inner weak shock appears irregularly with rapid variations due to the interaction of the expanding high magnetic blob with the accreting matter below the outer shock.…”
Section: Astrophysical Significancesupporting
confidence: 90%
See 2 more Smart Citations
“…The present results for cases with low resistivity of η = 10 −6 and 0.01 are very similar to those for the previous magnetized flow without resistivity (Okuda et al (2019)). Adopting the same parameters of the flow and magnetic field as the present study, they found that the centrifugally supported shock moves back and forth between 60 R g ≤ R ≤ 170R g and that another inner weak shock appears irregularly with rapid variations due to the interaction of the expanding high magnetic blob with the accreting matter below the outer shock.…”
Section: Astrophysical Significancesupporting
confidence: 90%
“…However, in many cases of the low angular momentum flow with the standing shock, h/r ∼ 0.1 -0.5 because such flows are intrinsically advective and geometrically thick. Therefore if the outer radial boundary is chosen to be very far from the predicted theoretical shock location, the difference between the numerical and theoretical shock locations becomes significant (Okuda et al (2019)).…”
Section: Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Molteni, Ryu & Chakrabarti (1996) showed through numerical simulation that when infall time scale matches with the cooling time scale of the accreting matter, resonance oscillation of PSC takes place. As PSC modulates, emergent hard radiations also exhibit non-steady variations which are in general quasi-periodic in nature (Lee, Ryu & Chattopadhyay 2011;Das et al 2014;Suková & Janiuk 2015;Suková, Charzyński & Janiuk 2017;Okuda et al 2019). Hence, the modulation of PSC perhaps be potentially viable to account for the QPO phenomena commonly observed in Galactic Black hole sources (Belloni, Psaltis & van der Klis 2002;Remillard et al 2006;Nandi et al 2012;Iyer, Nandi & Mandal 2015;Nandi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Accretion solutions of this kind contain more than one critical point, and hence, they are known as multi-transonic advective accretion solutions (Fukue 1987;Chakrabarti 1989;Das, Pendharkar & Mitra 2003;Das 2007). Needless to mention that numerous groups of researchers extensively studied the shock induced advective accretion solutions around black holes both theoretically as well as numerically (Fukue 1987;Chakrabarti 1989;Yang & Kafatos 1995;Molteni, Ryu & Chakrabarti 1996;Ryu, Chakrabarti, & Molteni 1997;Lu, Gu, & Yuan 1999;Becker & Kazanas 2001;Fukumura & Tsuruta 2004;Nishikawa et al 2005;Das 2007;Kumar, et al 2013;Das, et al 2014;Okuda & Das 2015;Suková & Janiuk 2015;Fukumura et al 2016;Sarkar & Das 2016;Aktar et al 2017;Dihingia et al 2018c;Kim et al 2018;Okuda, et al 2019).…”
Section: Introductionmentioning
confidence: 99%